Impact of High-Calorie, High-Protein Nutrition Education on Mothers’ Knowledge and Attitudes. - Susiatmi, Sandi Ari; Hasna, Khansa Mutiara (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
Stunting is defined as a short or very short body condition based on the index of Body Length by Age or Height by Age with a threshold (zscore) between -3 SD to -2 SD. The purpose of this study was to determine the effect of high calorie, high protein nutrition education on knowledge and attitudes in providing food to mothers who have stunted toddlers aged 24-59 months. This study used a pre-experimental design with a one group pre-test post-test design. The pre-experimental design includes one group and involves measurement before and after the intervention. The results of data analysis using paired t test to assess the knowledge and attitude of mothers in providing food to toddlers showed a significance value of p 0.000 (p < 0.05). This shows that nutrition education has a significant effect on increasing the knowledge and attitudes of mothers in providing food to toddlers. There is an influence on knowledge and attitude after being given education with statistical test results ρ = 0.000.Keywords: Stunting, Education, Knowledge, Attitude